Pericardiectomy and Mechanical Mitro-Aortic Valve Replacement in a Young Patient With Erdheim-Chester Disease - Nerea Lopez Perez, MBBS; Mathieu van Steenberghe, MD, PhD; Jörg D. Seebach, MD; Philippe Meyer, MD; Johannes Alexander Lobrinus, MD; Christoph Huber, MD; Mustafa Cikirikcioglu, MD, PhD (Texas Heart Institute Journal, 2024)
Erdheim-Chester disease is a rare histiocytosis that primarily affects the skeletal system, but cardiovascular manifestations occur in 75% of cases and are associated with a poor prognosis. Given the small number of cases, the evolution and management of the disease are uncertain. Therefore, it is important to report and share Erdheim-Chester cases. This report presents the case of a young patient with constrictive pericarditis and mitral valve regurgitation resulting from Erdheim-Chester disease.